(untitled) (Environment & Health, 2024)
The purpose of the study is a spatio-temporal analysis of the peculiarities of the national and regional dynamics of nutritional morbidity among the children of Ukraine. Research materials and methods: The study design included a retrospective analysis of official statistical data on the prevalence and incidence of food addiction in children and a review of the results of original studies. The research materials included statistical data of the State Statistics Service of Ukraine on certain food-dependent pathologies of the children’s population of Ukraine. The retrospective evaluation of statistical data was 18 years (2000-2017), national and regional data were evaluated. Research methods included statistical evaluation of factual and analytical material. The results: The analysis of trends in the prevalence and incidence of foodborne diseases in children in different age periods during 2000-2017 determines important features of the dynamics of these indicators in different age groups. The total share of alimentary diseases in the total structure of diseases is 9.88-10.00% at the age of 0-14 years old and 17.98% at the age of 15-17 years old. The general analysis shows a trend towards a decrease in the prevalence and incidence of food borne diseases among children of certain age groups over the course of 18 years. This especially applies to diseases of blood organs and the endocrine system. In the group of children aged 0-6 years old, there is an intense decrease in the registration of primary forms of diseases. At the age of 7-14 years old, during 2000-2017, there is an intensive decrease in the incidence and prevalence of diseases of the endocrine system and digestive organs, and at the age of 15-17 years old, there is a significant increase in growth and growth rates according to most indicators. Conclusions: the age-specific features of food-dependent pathology of the children’s population, spatial-temporal trends in national and regional sections are determined. The need for further research and monitoring in order to form a policy for the management of food-dependent pathology is shown.